Innovation Towards Circular Economy - A Theoretical Perspective - Van Hieu, Nguyen; Thi Hue, Hoang; Thi Anh Tuyet, Nguyen; Xuân Hoài, Võ; Thi Quynh Anh, Nguyen (VNU Journal of Science: Policy and Management Studies; Vol 39 No 3, 2023)
The transformation of the growth model, based on the foundation of innovation with a specific focus on transitioning towards a circular economy (CE), is a matter of significant importance for countries on a global scale, particularly those in the developing stage, such as Vietnam. This paradigm shift presents potential as an effective approach to addressing environmental and societal needs, while simultaneously fostering economic growth. It is widely acknowledged that innovation is a crucial tool in achieving a CE. This article elucidates the concept of innovation towards a CE by analyzing the existing concepts. Moreover, the article also clarifies forms of innovation towards a CE, encompassing four aspects: product innovation, process innovation, organizational innovation, and marketing innovation.